2018
DOI: 10.35608/ruraled.v34i1.406
|View full text |Cite
|
Sign up to set email alerts
|

How Do We Get Them on the Farm? Efforts to Improve Rural Teacher Recruitment and Retention in Arkansas

Abstract: Rural schools, particularly high poverty rural schools, often have difficulty hiring and retaining qualified teachers. Here, we discuss three programs the Arkansas Department of Education has used to attract teachers to teacher Geographic Shortage Districts (GSDs) through material incentives. Unfortunately, none of the programs have had much success, perhaps in part since the funding offered was inadequate to attract new teachers to isolated communities. Additionally, we analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…When examining the recruitment of teachers to rural schools, Maranto and Shuls (2013) found that websites should be used because they are the primary way someone from the outside learns about a new thing (Maranto & Shuls, 2013). These websites should include information about public service, freedom (innovation), advancement, professional growth, teamwork, results driven, and salary (Maranto & Shuls, 2013). While websites were not requested by the teachers, these critical areas mentioned in the article, can be applied to the materials that were requested.…”
Section: Discussionmentioning
confidence: 99%
“…When examining the recruitment of teachers to rural schools, Maranto and Shuls (2013) found that websites should be used because they are the primary way someone from the outside learns about a new thing (Maranto & Shuls, 2013). These websites should include information about public service, freedom (innovation), advancement, professional growth, teamwork, results driven, and salary (Maranto & Shuls, 2013). While websites were not requested by the teachers, these critical areas mentioned in the article, can be applied to the materials that were requested.…”
Section: Discussionmentioning
confidence: 99%
“…Research on teacher attrition has rarely considered rurality on its own (Monk, 2007) and has often included it simply as a covariate in regression models. The research that exists on teacher attrition in rural contexts employs qualitative research that is hard to generalize to other settings, uses small samples, considers only a subset of teachers, or conflates teacher intention or survey result for actual attrition behavior (Hammer et al, 2005;Lowe, 2006;Maranto & Shuls, 2013;Prater et al, 2007;Ulferts, 2016). For instance, Berry et al (2011) examined special education teacher recruitment and retention in rural 3 districts by conducting telephone interviews with 203 special educators.…”
Section: Teacher Attrition In Rural Contextsmentioning
confidence: 99%
“…Although financial incentives may initially entice teachers to teach in rural areas, the lasting power of the incentive tends to wane over time. In fact, Maranto and Shuls (2012) found that all three of Arkansas’s incentive programs were ineffective in recruiting and retaining teachers to work in rural shortage districts, perhaps because the rather substantial monetary incentives were still insufficient.…”
Section: Strategies For Addressing Set Shortages In Rural Schoolsmentioning
confidence: 99%